Localization of Nucleoporin Tpr to the Nuclear Pore Complex Is Essential for Tpr Mediated Regulation of the Export of Unspliced RNA - Rajanala, Kalpana (Public Library of Science, 2012)
Nucleoporin Tpr is a component of the nuclear pore complex (NPC) that localizes exclusively to intranuclear filaments. Tpr functions as a scaffolding element in the nuclear phase of the NPC and plays a role in mitotic spindle checkpoint signalling. Export of intron-containing mRNA in Mason Pfizer Monkey Virus is regulated by direct interaction of cellular proteins with the cis-acting Constitutive Transport Element (CTE). In mammalian cells, the transport of Gag/Pol-CTE reporter construct is not very efficient, suggesting a regulatory mechanism to retain this unspliced RNA. Here we report that the knockdown of Tpr in mammalian cells leads to a drastic enhancement in the levels of Gag proteins (p24) in the cytoplasm, which is rescued by siRNA resistant Tpr. Tpr's role in the retention of unspliced RNA is independent of the functions of Sam68 and Tap/Nxf1 proteins, which are reported to promote CTE dependent export. Further, we investigated the possible role for nucleoporins that are known to function in nucleocytoplasmic transport in modulating unspliced RNA export. Results show that depletion of Nup153, a nucleoporin required for NPC anchoring of Tpr, plays a role in regulating the export, while depletion of other FG repeat-containing nucleoporins did not alter the unspliced RNA export. Results suggest that Tpr and Nup153 both regulate the export of unspliced RNA and they are most likely functioning through the same pathway. Importantly, we find that localization of Tpr to the NPC is necessary for Tpr mediated regulation of unspliced RNA export. Collectively, the data indicates that perinuclear localization of Tpr at the nucleopore complex is crucial for regulating intron containing mRNA export by directly or indirectly participating in the processing and degradation of aberrant mRNA transcripts.